The Power of Illusion in the Play "The Kingdom of the Raven" by Azeddine Jlaouji: A Cultural Critical Approach to the Cover Threshold - ahmadi, Leila; Laib, Youcef (LANGUAGE ART, 2026)
This research aims to examine the cover of the play "The Kingdom of the Raven" by AzeddineJlaouji through the lens of cultural criticism. The significance of this study lies in its focus on the cover threshold as a tool for cultural-critical reading, revealing the underlying cultural structures embedded within the text’s deep layers and bringing them to the surface. This analysis employs a new critical approach that goes beyond the literary and aesthetic aspects to explore the text from a cultural perspective, with the objective of interrogating the deeply rooted cultural patterns within. The cover, as one of the key textual thresholds, plays a vital role in interpreting the text, decoding its symbols, and uncovering its hidden messages. This study focuses on the cover threshold due to its capacity to convey intellectual and cultural content through an aesthetic framework. The cover presents itself as a cultural system laden with implicit and unspoken elements that demand a culturally critical reading to unveil the concealed discourse. The cover threshold of the play "The Kingdom of the Raven" by AzeddineJlaouji emerges as a phenomenon worthy of cultural examination, as it employs symbolic vision using the aesthetics of imagery, form, color, and language. This cover conceals a dominant cultural pattern operating covertly—the power of illusion—which has come to control minds within Arab societies, acting as a significant obstacle to progress, creativity, and innovation. Additionally, the cover reflects an underlying call to awaken the Arab self, encouraging it to confront its backward reality and strive toward reform and advancement.